2012
DOI: 10.1593/neo.121262
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Pharmacologic Inhibition of Complement Impairs Endothelial Cell Function and Ablates Ovarian Cancer Neovascularization

Abstract: Complement activation plays a critical role in controlling inflammatory responses. To assess the role of complement during ovarian cancer progression, we crossed two strains of mice with genetic complement deficiencies with transgenic mice that develop epithelial ovarian cancer (TgMISIIR-TAg). TgMISIIR-TAg mice fully or partially deficient for complement factor 3 (C3) (Tg(+)C3(KO) and Tg(+)C3(HET), respectively) or fully deficient for complement factor C5a receptor (C5aR) (Tg(+)C5aR(KO)) develop either no ovar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
124
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(132 citation statements)
references
References 59 publications
7
124
0
1
Order By: Relevance
“…30,31,43 Our immunohistochemistry data showed a marked deposition of C1q on vascular endothelium and stroma of neuT tumors. On the other hand, the increased tumor vascularization observed in neuT-C1KO mice suggests that C1q could be considered an inhibitor of tumor angiogenesis, at least in our model of autochthonous Her2/neu-driven mammary cancer that display a process of angiogenesis 44 not superimposable to that observed in transplantable tumors.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…30,31,43 Our immunohistochemistry data showed a marked deposition of C1q on vascular endothelium and stroma of neuT tumors. On the other hand, the increased tumor vascularization observed in neuT-C1KO mice suggests that C1q could be considered an inhibitor of tumor angiogenesis, at least in our model of autochthonous Her2/neu-driven mammary cancer that display a process of angiogenesis 44 not superimposable to that observed in transplantable tumors.…”
Section: Discussionmentioning
confidence: 58%
“…It has been demonstrated that cancer cells establish a balance between complement activation and inhibition. 29 However, controversial and conflicting data on the complement system's tumor-promoting, 30,31 and inhibiting activities, 24 have been published, 2 and the mechanisms of complement-specific activities in the tumor microenvironment are still unclear and demands further study.…”
Section: Discussionmentioning
confidence: 99%
“…Complement is now thought to be a key component of cancer-related inflammation, and a recent study has suggested that exacerbated inflammation in the tumor microenvironment promotes genetic instability (25). The canonical proinflammatory mediator C5a has been widely implicated for a role in tumor growth, with both tumor-promoting and tumor-inhibitory effects reported, depending on tumor type, immune status of the host, and C5a levels (6)(7)(8)(9)26). Although these and other studies (27) have shown that tumor growth is reduced in the absence of C3 (which generates both C3a and C5a), the tumor-promoting effects have been attributed solely to C5a.…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon has motivated several researchers to look into therapeutically inhibiting angiogenesis in an attempt to restrain tumor growth. Furthermore, the activation of both angiogenesis and immunosuppressive responses, often occur in the same cell types or are mediated by the same soluble factors (69 (72). The proangiogenic effect of complement was further supported by the finding that C5a induced vessel formation in 3LL cells (65).…”
Section: The Dual Role Of Complement In Angiogenesismentioning
confidence: 90%